Efecto de la adición de harina de Cyperus rotundus “Coquito” sobre los parámetros productivos de Pavos - Rocha Romero, Marilly Fiorella (2019)
This investigation was carried out in the Chual farm, located in the Caserío of the same name, District of Simbal, Province of Trujillo, La Libertad Region, with the objective of evaluating the effect of the addition of Cyperus rotundus "Coquito" in diets on the turkeys production parameters. For which 180 mixed turkeys of the Hybrid line distributed in three treatments under a completely random design were used. The treatments were: T0: 0,05 kg Zin-bacitracin / t of food, T1: 1 kg of Coquito flour / t of food, T2: 2 Kg of coquito flour / t of food. In the weekly weights parameter, the T0 was higher in all the weeks, but only significant statistical differences were calculated (P<0,05) in the second (0,91 kg) and ninth week (5,37 kg), and were calculated highly significant statistical differences (P <0,01) in the third week (0,91 kg). In the final weight parameter, the T0 had the highest weight (11,69 kg), followed by T2 (11,2 kg) and T1 (10,68 kg), significant statistical differences were calculated (P <0,05). In the food intake parameter, T1 had the highest consumption (23,01 kg), followed by T2 (22,96 kg) and T0 (22,93 kg), no significant statistical differences were calculated (P>0,05). In the feed conversion parameter, the T0 was higher (2,4), followed by T2 (2,5) and T1 (2,6), significant statistical differences were calculated (P<0,01). In the mortality percentage parameter, the T0 had a 1.1% mortality, the T1 with 1.7%, and the T2 had 2.2%. No significant statistical differences were calculated (P>0,05). In housing performance, T0 had the highest performance with 76%, T2 with 75,5% and T1 with 75,3%. No significant statistical differences were calculated (P>0,05). The productive efficiency index was better in the T0 with 420,3; followed by T2 with 375 and T1 with 348,5. It is concluded that the inclusion of Cyperus rotundus in diets does not improve the productive parameters in turkeys.